2007
DOI: 10.2298/avb0706413p
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunity evaluation in piglets originating from sows vaccinated with China strain of classical swine fever virus

Abstract: An experimental study was conducted to investigate the course of classical swine fever (CSF) infection in piglets originating from sows vaccinated with China strain vaccine. The experiment was carried out on 24 piglets (age 28, 35, 44 and 54 days) from vaccinated sows and on 11 non vaccinated piglets, originated from non CSF vaccinated sows. Two piglets from the each age group originating from vaccinated sows were challenged by intramuscular injection with CSF virus. Four piglets of the same age from vaccinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…It was found that 5'UTR region of CSFV was amplified in 10 samples, collected from infected animals on day 6 th and 9 th post infection only. This is in agreement with Jasna et al (2007) who reported that CSFV antigen (viraemia) is detected on 7 th and 9 th dpi by ELISA in piglets of different age group (28, 35, 44 and 54 days old) exposed to contact infection of CSFV and these findings were confirmed by applying RT-PCR technique, the presence of viral RNA was detected only in 3 piglets from blood samples. Hence detectable level of CSFV antigen was observed on day 6-7 th post infection and gradually increased till death.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 92%
“…It was found that 5'UTR region of CSFV was amplified in 10 samples, collected from infected animals on day 6 th and 9 th post infection only. This is in agreement with Jasna et al (2007) who reported that CSFV antigen (viraemia) is detected on 7 th and 9 th dpi by ELISA in piglets of different age group (28, 35, 44 and 54 days old) exposed to contact infection of CSFV and these findings were confirmed by applying RT-PCR technique, the presence of viral RNA was detected only in 3 piglets from blood samples. Hence detectable level of CSFV antigen was observed on day 6-7 th post infection and gradually increased till death.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 92%
“…In infected piglets, course of the disease was influenced by the virulence of the virus and symptoms may vary hence, the antigen ELISA, based on the detection of viral antigen (Depner et al 1995) and molecular technique RT-PCR based become helpful for rapid detection of CSFV (Le Dimna et al 2008). A challenge study revealed that virus in blood can be detected in blood collected on 6-7th day post infection (dpi) by antigen ELISA and RT PCR (Jasna et al 2007, Raut et al 2015, while, typical symptoms of CSF (anorexia, conjunctivitis, in-coordination, diarrhea, reddening of the base of ear etc) were observed 10-12 dpi onwards (Cariolet et al 2008, Raut et al 2015. So, it is very much necessary to create awareness among the pig farmers to submit blood samples along with tissue samples to the reference diagnostic laboratories for diagnosis of CSF.…”
Section: Resultsmentioning
confidence: 99%